Dissolved cerium contributes to uptake of Ce in the presence of differently sized CeO2-nanoparticles by three crop plants1. Issue 3 (11th March 2015) - Schwabe, Franziska; Tanner, Simon; Schulin, Rainer; Rotzetter, Aline; Stark, Wendelin; von Quadt, Albrecht; Nowack, Bernd
<x xml:space="preserve">Abstract</x> Cerium uptake into plants in the presence of CeO2 nanoparticles occurs not only in nanoparticulate form, but also as dissolved ions.